Моделирование параметров и характеристик световых приборов на основе энергосберегающих светодиодных источников света - Говоров, Ф.П.; Носанов, Н.И.; Романова, Т.И.; Король, О.В. (Технічна електродинаміка, 2012)
Developed the algorithm and the program of calculation of lighting devices based on light-emitting light sources, calculation results are presented round symmetrical led device.